2004
DOI: 10.1111/j.1600-051x.2004.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of gingivitis and periodontitis with ischemic stroke

Abstract: Periodontitis is an independent risk factor for cerebral ischemia and acute exacerbation of inflammatory processes in the periodontium might be a trigger for the event of cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 36 publications
5
107
1
6
Order By: Relevance
“…Smin et al performed measurements at six sites of each tooth present, while other researchers evaluated four sites [45,46,48,49,50]. All these researchers have confirmed that the risk of stroke increases proportionally to the loss of CAL.…”
Section: State Of Knowledgementioning
confidence: 77%
See 4 more Smart Citations
“…Smin et al performed measurements at six sites of each tooth present, while other researchers evaluated four sites [45,46,48,49,50]. All these researchers have confirmed that the risk of stroke increases proportionally to the loss of CAL.…”
Section: State Of Knowledgementioning
confidence: 77%
“…The authors performed clinical (gingival index, BoP, probing depth, CAL) and radiological (bone loss) periodontal examinations [12,45,46,47,48,49,50]. The methodological differences were also demonstrated at the level of stroke diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations